Conteúdos de ensino da educação física escolar : da produção acadêmica às narrativas docentes - Matos, Juliana Martins Cassani (2013)
It has as objective the understanding of the relationship between the teaching contents and the specificity of Physical Education. It is characterized by a multi-methodological qualitative and quantitative approaches and was delineated into three chapters that interact with each other, considering the nature of the studied sources and assumed theoretical and methodological presuppositions. In a type of "state of knowledge", the first chapter investigates the academic productions that deal with the contents of teaching in school Physical Education in the period 1981-2010. The 146 items mapped are distributed in 14 journals analyzed by bibliometric indicators (Mugnaini; Oak; Campanatti-Ostiz, 2006). Research indicates the authors that are numerical reference in the field and their relationship with the Post Graduate Programs, their lines of study and research groups that offer theoretical and methodological support. The second chapter, of a qualitative and quantitative nature, discusses the opinion of 266 physical education teachers in the State of Espirito Santo on the processes of selection and systematization of the teaching contents, expressed in a questionnaire with closed and semi-open questions. It gives visibility to approximations to the contents with the local culture and the implications of the logic of schooling in choosing what and when to teach. The third chapter is characterized by a narrative research (Certeau, 2002; Ribeiro; Souza, 2010) and evidences how the physical education teachers work with teaching contents. It has 14 Physical Education teachers as collaborators working in the Basic Education of the Metropolitan microrregion the State of Espírito Santo, and, for the production of sources, it uses a semistructured interview, a focal group and three to five individual oral narratives. Teachers make explicit the privileged knowledge by the discipline as those embodied by the imbrication of Themselves in the situation and by the distancing-regulation (CHARLOT, 2000). By giving visibility to educational projects developed by teachers, the research shows possibilities of setting up a curriculum integration through themes that permeate different disciplines